The Mother City of Jewish Public Life: Zalmen Reyzen’s Image of Interwar Vilna - Kassow, Samuel D. (Colloquia, 2021)
A specific vision of Vilna as the model of an East European Jewish civil society crystallised in the years during and just after the First World War, and Vilna’s professional elites and journalists played a critical role in the crafting and shaping of this idea. This paper shows how Zalmen Reyzen, a leading Vilna Yiddishist intellectual who edited Vilna’s most important Yiddish daily between the wars, Der tog (1919–1939), tirelessly sought to convince others that Vilna had a special role to play as a model for the entire Jewish Diaspora, as a city uniquely suited to build a Jewish civil society based on a shared language, Yiddish. Reyzen told his readers in articles and editorials that the collapse of the tsarist regime gave Jews an unprecedented chance to build a new secular school system, create a new democratic communal board (kehile), and break the stranglehold of old communal elites.